Probiotic effect of PROBIOLACTlL®, SUBTILPROBIO® and their mixture on productive and health indicators of growing pigs - Rondón, Ana J.; Socorro, Marvelys; Beruvides, A.; Milián, Grethel; Arteaga, Fátima; Vera, R. (Cuban Journal of Agricultural Science, 2020)
To evaluate the probiotic effect of PROBIOLACTlL®, SUBTILPROBIO® biopreparations and their mixture, on productive and health indicators in growing pigs, an experiment with a completely randomized design was developed, with four treatments: 1 control) basal diet without additives, 2) basal diet + PROBIOLACTIL®, 3) basal diet + SUBTILPROBIO® and 4) basal diet + mixture of both biopreparations. As a result, it was confirmed that these additives and their mixture improved all indicators. Better effects were manifested in pigs that consumed PROBIOLACTIL®. The evaluated biopreparations produced benefits in animals, since they improved eubiosis of the gastrointestinal tract, which contributed to improve (P <0.05) live weight (27.15 kg/25.59 kg), daily mean gain of animals (408.65g/445.27g), weight gain (19.42kg/16.36 kg) and food conversion (2.44/2.90). Furthermore, the incidence of diarrhea decreased (8.57/67.14 %) in treated animals. Results confirm the probiotic potential of these biopreparations, when applied to pigs during growth stage, with better effects on those that consumed PROBIOLACTIL®. Key words: probiotics, Lactobacillus, Bacillus, zootechnical additives, pig farming